Nursing of a patient with chronic eczema treated by acupoint injection technique (穴位注射护理技术治疗1例慢性湿疹患者的护理体会) - CHEN Lu (陈璐); SUN Mingli (孙明丽) (中西医结合护理)
This paper summarized the application effect of Traditional Chinese Medicine(TCM) acupoint injection technique and related nursing management for a patient with chronic eczema and skin lesions. Nursing assessment and health education about injection method and precautions were carried out. Under the guidance of TCM syndrome differentiation and nursing theory, acupoint injection technique was adopted to relieve the pruritus symptoms and improve the recovery from skin lesions in patient with chronic eczema. (本文总结了1例慢性湿疹瘙痒及皮损患者行穴位注射的效果观察及护理措施, 包括护理评估、穴位注射方法及注意事项、常规护理措施等。基于中医辨证施护理论开展护理干预, 有助于改善慢性湿疹患者瘙痒症状, 促进皮损好转。)